Pengembangan Modul Kewirausahaan Bagi Tenant Inkubator Bisnis: Pendekatan Model Analysisi Desing Development Implementation Evaluation (ADDIE) - Amelia Hidayah; Fanny Suzuda Pohan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
University business incubator has become a place for many entrepreneurs to develop innovative products. However, several problems are experienced by tenants including capital, lack of business ability, poor of performance teams. Facing tenant problems related lack of business ability can be overcome by training and coaching. Therefore, researchers try to develop entrepreneurship modules for university business incubators. The research applies ADDIE (Analyzing, Designing, Developing, Implementation, and Evaluation) model. There are five major phases that are carried out starting from identifying training topics, designing a module, creating modules and questionnaires, providing entrepreneurship training, and evaluating modules. After going through 5 stages, the research produces 3 entrepreneurship modules, namely business models, financial understanding, and winning markets through digital marketing. These three modules are delivered in training activity which are divided into three sessions. After attending training, the participants respond that the modules are structured in terms of content and their benefits in improving management skills.